Characteristics of Envelope Genes in a Chinese Chronically HIV-1 Infected Patient With Broadly Neutralizing Activity - Zhang, Dai; Zou, Sen; Hu, Yuanyuan; Hou, Jiali; Hu, Xintao; Ren, Li; Ma, Liying; He, Xiang; Shao, Yiming; Hong, Kunxue (Frontiers in Microbiology, 2019)
Exploring the characteristics of the HIV-1 envelope glycoprotein (env) gene in a natural HIV-1 infected individual, with broadly neutralizing activity, may provide insight into the generation of such broadly neutralizing antibodies and initiate the design of an appropriate immunogen. Recently, a chronically HIV-1 infected patient with broadly neutralization activity was identified and a VRC01-class neutralizing antibody DRVIA7 (A7) was isolated from the patient. In the present study, 155 full length HIV-1 env gene fragments (including 68 functionally Env clones) were amplified longitudinally from the plasma of six time points spanning over 5 years in this donor. Viral features were analyzed by comparing Env clones of different time points, as well as 165 Chinese HIV-1 subtype B env sequences from HIV Sequence Database (Chinese B_database). Shorter V1 length, less potential glycan and a lower ratio of NXT: NXS in gp160 were observed in the first five time points compared to that from the last time points, as well that from the Chinese B_database. A sequence analysis and a neutralization assay of Env-pseudoviruses showed that the increasing diversity of env sequences in the patient was consistent with the appearance and maturation of A7 lineage antibodies. The potent neutralization activity and viruses that escaped from the neutralization of the concurrent autologous plasma, are consistent with higher residue variations at the antibody recognition sites. Almost all viruses from the plasmas were neutralization-resistant to VRC01 and A7 lineage antibodies. For a chronically HIV-1 infected individual over 10 years, we found that greater viral diversity, short V1 sequences and less potential N-linked glycosylation (PNGS) in V1, might be associated with the development of broadly neutralizing antibody responses.